Application of disposable plastic microfluidic device arrays with customized chemistries to multiplexed biochemical assays. (April 2002) - Ricco, A. J.; Boone, T. D.; Fan, Z. H.; Gibbons, I.; Matray, T.; Singh, S.; Tan, H.; Tian, T.; Williams, S. J.
Abstract : Plastic microfluidic array platforms and synergistic multiplexed assay chemistries are under development for a variety of applications, including assays of gene expression, proteomics, genotyping, DNA sequencing and fragment analysis, sample prepraration and high-throughput pharmaceutical discovery. The low production costs of plastic substrates makes possible economical single-use device arrays, eliminating cleaning and sample-to-sample carryover contamination. Hundreds of microchannels and reservoirs are readily included on a single microtitre-plate-size substrate, enabling the manufacture of highly parallel fluidic array systems to increase throughput and speed.